PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS-ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN KOMUNIKASI MATEMATIKA SISWA KELAS VIIA3 MTS DARUL HIKMAH PEKANBARU - Mentari Tiara Putri; Rini Dian Anggraini; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is based on the low yield of learning mathematics in class VIIA3 MTs Darul Hikmah Pekanbaru, there are 7 of 25 students who achieved the Minimum Mastery Criteria or 28% for linear equations and inequalities of one variable. The type of this research is classroom action research. The purpose of this research is to improve the learning process and improve communication skills by applying mathematical models of cooperative learning Student Teams-Achievement Divisions (STAD). The subject of this research were the students in class VIIA3 MTs Darul Hikmah Pekanbaru at the first semester of academic year 2014/2015. The instruments of data collection in this research were observation sheets and mathematical understanding tests. The observation sheets were analyzed in qualitative descriptive. The qualitative descriptive showed that there is the improvement of learning process after the action on the first and second cycles. The result showed that there is an increase the mathematical understanding of students with the score N-gain is 0,63 in the first cycle and 0,76 in the second cycle at medium classification. The conclusion of this research is the implementation of cooperative Student Teams-Achievement Divisions (STAD) to improve mathematical communication graders understanding of students in class VIIA3 MTs Darul Hikmah Pekanbaru in the first semester of academic year 2014/2015.Key Word : Mathematical communication skills, cooperative learning Student Teams Achievement Divisions (STAD)